A Monte Carlo Comparison between the Free Cash Flow and Discounted Cash Flow Approaches - Mehari Mekonnen Akalu; Rodney Turner (Tinbergen Institute, 2002)
One of the debates in the capital budgeting model selection is between the free cash flow and DCF methods. In this paper an attempt is made to compare SVA against NPV model based on Monte Carlo simulations. Accordingly, NPV is found less sensitive to value driver variations and has got higher forecast errors as compared to SVA model.
Keywords: G30; G31; L6; L8; L9; M10; O22; O32; 330; Capital budgeting; Investment appraisal; DCF methods; Project Analysis; Shareholder Value Analysis; Value Management Techniques.; Cash Flow; Betriebliche Budgetierung; Projektbewertung; Wertanalyse; Monte-Carlo-Methode; Theorie